2018
DOI: 10.1186/s40851-018-0096-9
|View full text |Cite|
|
Sign up to set email alerts
|

A comprehensive comparison of sex-inducing activity in asexual worms of the planarian Dugesia ryukyuensis: the crucial sex-inducing substance appears to be present in yolk glands in Tricladida

Abstract: BackgroundTurbellarian species can post-embryonically produce germ line cells from pluripotent stem cells called neoblasts, which enables some of them to switch between an asexual and a sexual state in response to environmental changes. Certain low-molecular-weight compounds contained in sexually mature animals act as sex-inducing substances that trigger post-embryonic germ cell development in asexual worms of the freshwater planarian Dugesia ryukyuensis (Tricladida). These sex-inducing substances may provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…When the marine flatworm Thysanozoon brocchii , which does not have an ectolecithal egg system, and the slug Ambigolimax valentianus (non-flatworm tissue) were fed to D. ryukyuensis , none exerted a sex-inducing effect able to fully sexualize the worms. 15 These results suggest that vitellocytes are important for the production and/or storage of sex-inducing substances and that sex-inducing substances are conserved within species with an ectolecithal egg system. 15 Therefore, parasitic flatworms, which do have an ectolecithal egg system ( Figure 1 A), are expected to contain sex-inducing substances.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…When the marine flatworm Thysanozoon brocchii , which does not have an ectolecithal egg system, and the slug Ambigolimax valentianus (non-flatworm tissue) were fed to D. ryukyuensis , none exerted a sex-inducing effect able to fully sexualize the worms. 15 These results suggest that vitellocytes are important for the production and/or storage of sex-inducing substances and that sex-inducing substances are conserved within species with an ectolecithal egg system. 15 Therefore, parasitic flatworms, which do have an ectolecithal egg system ( Figure 1 A), are expected to contain sex-inducing substances.…”
Section: Introductionmentioning
confidence: 83%
“…Images are of the flatworm species used in the present study. Bdellocephala brunnea (class Turbellaria, order Tricladida, family Dendrocoelidae) was already known to harbor sex-inducing substances 11 , 15 and, thus, was used as a positive control. Monogeneans (Monogenea): Neoheterobothrium hirame (order Mazocraeidea, family Diclidophoridae) and Neobenedenia girellae (order Capsalidea, family Capsalidae).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ] the author advised that unfortunately in the ‘Discussion’ section the letters ‘L’ and ‘D’ in some ‘enantiomer’ expressions were not written in the format of ‘small capitals’. Rather, they were written as lower-case letters.…”
Section: Correctionmentioning
confidence: 99%
“…In a previous study, we found that the feeding of fresh cocoons containing numerous yolk gland cells to asexual worms caused their full sexual induction [ 22 ]. This result suggests that yolk gland cells might contain sex-inducing substance(s) that trigger full sexual induction.…”
Section: Introductionmentioning
confidence: 99%